Your blood is our blood: The metaphorical extensions of ‘Lucho’ Herrera’s glory - Linares, Nicolás Lliano (Academic Quarter | Akademisk kvarter, 2015)
On July 12 of 1985 at Saint-Étienne, France, Luis Alberto ‘Lucho’ Herrera, the first Colombian cyclist to have won a Tour de France stage (1984), became an international hero and a national martyr. Not only did the image of Herrera’s bloodied face staring at the horizon after winning the 14th stage acquire cult status within cycling circles around the world, it also established a subtle, yet passionate, connection between the figure, his performance, and Colombian reality. We argue that Herrera’s image worked as a metaphorical extension that stimulated the association between Herrera’s martyred image and the collective struggle people had to go through on a daily basis, accentuating the strongly Catholic iconographic dimension attached to popular sport practices in Colombia (faith, endurance, and suffering). Using applied elements of Charles S. Peirce’s semiotic apparatus, this paper analyze three symbolic elements embedded in Herrera’s image – blood, struggle, and redemption – to discuss the photograph’s power to resonate with the average Colombian at a time when narco terrorism ruled most of the territory and the escalation of insurgency and paramilitary violence were daily occurrences.